Lance Flies (Diptera: Lonchaeidae) Associated with Acca Sellowiana (Myrtaceae) in Lages, Santa Catarina, Brazil - Souza G.K.* (2019)
© 2019 Florida Entomological Society. All rights reserved.This study documents the species of lance flies (Diptera: Lonchaeidae) associated with fruits of feijoa (Acca sellowiana [Berg] Burret) (Myrtaceae), as well as their infestation level in an orchard located in Lages, Santa Catarina, Brazil. Neosilba bifida, N. delvechioi, and N. pradoi are reported for the first time damaging fruits of feijoa. Moreover, this is the first report of the presence of N. bella, N. bifida, and N. delvechioi from the state of Santa Catarina.